Transfusion or Timing: The Role of Blood Volume in Delayed Cord Clamping During the Cardiovascular Transition at Birth - Stenning, Fiona J.; Hooper, Stuart B.; Kluckow, Martin; Crossley, Kelly J.; Gill, Andrew W.; Wallace, Euan M.; te Pas, Arjan B.; LaRosa, Domenic; Polglase, Graeme R. (Frontiers in Pediatrics, 2019)
Placental transfusion has been thought to be the main benefit of delayed umbilical cord clamping (DCC) in preterm neonates. However, the importance of cardiovascular stability provided by allowing lung aeration prior to cord clamping has recently been highlighted. We aimed to determine the influence of blood volume changes on cardiovascular stability at birth. Preterm lambs (0.85 gestation) were instrumented for measurement of pulmonary, systemic and cerebral blood pressures and flows, systemic oxygen saturation and cerebral oxygenation. Left ventricular output (LVO) was assessed by Doppler Echocardiography. Lambs underwent immediate cord clamping followed by 1) 25ml/kg infusion of whole blood over 90s; or 2) withdrawal of 10 ml/kg blood over 90s. Ventilation was initiated 30s after volume change (2 minutes after cord clamping) and was maintained for 30 minutes. Blood infusion significantly increased pulmonary blood flow which maintained systemic cardiac output during the infusion, and increased carotid arterial pressure, flow and heart rate, which remained elevated until after ventilation onset. Upon completion of transfusion PBF rapidly returned to control levels and LVO decreased. Conversely, blood withdrawal decreased PBF and LVO. The cardiovascular changes that accompanied ventilation onset were similar between groups. Providing a blood volume transfusion immediately after umbilical cord clamping maintains PBF and cardiac output during the transfusion, which does not persist beyond the period of the transfusion. Our study implies that an apneic newborn cannot maintain cardiac output through an increase blood volume alone. Importantly, delaying umbilical cord clamping until after breathing/aeration of the lung may be a way to maintain cardiac output throughout delivery at birth.